2010
DOI: 10.3945/jn.109.113779
|View full text |Cite|
|
Sign up to set email alerts
|

Guidance for Substantiating the Evidence for Beneficial Effects of Probiotics: Current Status and Recommendations for Future Research1–3

Abstract: Probiotic bacteria are live microorganisms that, when administered in adequate amounts, confer a health benefit on the host. There is a growing interest in probiotics within the scientific community, with consumers, and in the food industry. The interactions between the gut and intestinal microbiota and between resident and transient microbiota define a new arena in physiology, an understanding of which would shed light on the "cross-talk" between humans and microbes. The different beneficial effects of specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
144
0
13

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(159 citation statements)
references
References 26 publications
(32 reference statements)
2
144
0
13
Order By: Relevance
“…Mixtures of these strains are becoming increasingly popular as researchers gain a deeper understanding of increasing efficacy via possible additive or synergistic effects [124]. Rijkers et al categorised the benefit of probiotics into three levels based on location and method; (1) interference with the growth or survival of pathogenic microorganisms in the gut lumen, (2) improvement of mucosal barrier function or mucosal immune system and (3) influence beyond the gut through the systemic immune system and other organs [125]. A study undertaken by Park et al found that DIO mice treated with the probiotic strains Lactobacillus curvatus HY7601 and Lactobacillus plantarum KY1032 experienced reduced body weight gain and fat accumulation in addition to lowered plasma insulin, leptin, total-cholesterol and liver toxicity biomarkers compared to a group on the same diet supplemented with a placebo [126].…”
Section: Modulation By Probioticsmentioning
confidence: 99%
“…Mixtures of these strains are becoming increasingly popular as researchers gain a deeper understanding of increasing efficacy via possible additive or synergistic effects [124]. Rijkers et al categorised the benefit of probiotics into three levels based on location and method; (1) interference with the growth or survival of pathogenic microorganisms in the gut lumen, (2) improvement of mucosal barrier function or mucosal immune system and (3) influence beyond the gut through the systemic immune system and other organs [125]. A study undertaken by Park et al found that DIO mice treated with the probiotic strains Lactobacillus curvatus HY7601 and Lactobacillus plantarum KY1032 experienced reduced body weight gain and fat accumulation in addition to lowered plasma insulin, leptin, total-cholesterol and liver toxicity biomarkers compared to a group on the same diet supplemented with a placebo [126].…”
Section: Modulation By Probioticsmentioning
confidence: 99%
“…Более того, способность их приживаться в кишечнике на длительный срок ставится под сомнение, поскольку, как уже отме-чалось, состав индигенной флоры во многом определен генетически и основан на тонких иммунных взаимодей-ствиях с макроорганизмом [1,2,7]. Выделяют следующие основные механизмы положительных эффектов пробио-тиков [30], которые осуществляются на разных уровнях воздействия.…”
Section: механизм действия пробиотиковunclassified
“…При этом направленность влияния на иммунный ответ неодинакова для разных пробиотиков. Так, L. casei слу-жит мощным стимулятором продукции IL 6, IL 12, TNF ␣ и экспрессирует маркеры созревания, тогда как L. reuteri является слабым индуктором IL 12, подавляет секрецию цитокинов и экспрессию маркеров созревания, вызван-ную другими видами лактобактерий [30]. Часть положи-тельных эффектов пробиотиков обеспечивают их мета-болиты [24].…”
Section: механизм действия пробиотиковunclassified
See 1 more Smart Citation
“…Through genetic engineering, it is possible to strengthen the effect of existing probiotic [8] strains and create completely new probiotics [9] with multiple health benefits These natural or genetically engineered beneficial bacteria might alter the ratio of "good to bad bacteria "that inhabit the intestine, and might specifically block activity of food borne pathogens to prevent of gastrointestinal diseases. (Table 1) Biotechnology refers to the use of living organisms to make useful products, and overlaps with bioengineering and industrial microbiology [1].…”
mentioning
confidence: 99%